Science Reading Habits, Learning Interest, and Their Effect on Students’ Academic Achievement - Siti Halimatussoleha; Badrul Jihad; Muhamad Samsul Hadi; Dede Prianto (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
Academic achievement in elementary science is influenced by multiple cognitive and motivational factors that interact within the learning process. This study aims to examine the relationships and predictive roles of reading frequency and students’ interest in science learning on academic achievement in the topic of animal reproduction among sixth-grade students. The study employed a quantitative survey design involving 37 students, with data collected through questionnaires and achievement tests and analyzed using correlational and regression approaches. The findings indicate that reading frequency and learning interest do not show significant relationships with academic achievement when examined individually; however, both variables demonstrate a significant combined predictive association when analyzed simultaneously. This suggests that academic achievement is shaped by the interaction of cognitive engagement and motivational factors rather than by isolated variables. These results highlight the importance of integrating reading activities with strategies that foster meaningful learning interest. It is recommended that future research explore additional mediating variables and apply more comprehensive analytical models to better understand the mechanisms underlying students’ academic achievement in science education.